Incidental Diagnosis of a Rare Case of Corkscrew Aorta. (13th October 2019) - Petullà, M.; Mazzarella, G.; Critelli, L.; Paone, L.; Laganà, D.
Abstract : The corkscrew aorta is a variant of the normal anatomical course of the aorta. This rare condition is characterized by a marked tortuosity of the aorta. In our experience it concerns the tract of subrenal aorta, that is an unusual condition, since there are no other cases in the literature. It is characterized by the presence of at least two kinking, and a coiling interposed among them. It is diagnosed by Angio-CT and its response is incidental, being from an asymptomatic clinical point of view.